2018
DOI: 10.1002/jaal.923
|View full text |Cite
|
Sign up to set email alerts
|

What Can Parents Tell Us About Poverty and Literacy Learning? Listening to Parents Over Time

Abstract: In this article, the authors use Bourdieu's conceptualization of capital and data from two longitudinal case studies to explore how financial challenges impacted learning opportunities for two children in a high‐poverty urban community. Interview data collected from two African American families over a 10‐year period were analyzed with attention to the role of economic academic capital (resources and experiences that require financial investment and translate to school success) in children's school trajectorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Throughout these various forms of mentorship, parents mostly inhabited a teacher role by providing resources, verbal encouragement, and digital restrictions, hoping to augment their sons’ engagements with school-sanctioned literacy. This article reinforces the body of literature disputing the idea that low-income families are not involved in school-sanctioned literacies in their homes (Compton-Lilly, 2012; Compton-Lilly & Delbridge, 2019) and adds to the richness of the body of family literacy studies (Lewis, 2011; Lewis Ellison & Wang, 2018).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Throughout these various forms of mentorship, parents mostly inhabited a teacher role by providing resources, verbal encouragement, and digital restrictions, hoping to augment their sons’ engagements with school-sanctioned literacy. This article reinforces the body of literature disputing the idea that low-income families are not involved in school-sanctioned literacies in their homes (Compton-Lilly, 2012; Compton-Lilly & Delbridge, 2019) and adds to the richness of the body of family literacy studies (Lewis, 2011; Lewis Ellison & Wang, 2018).…”
Section: Discussionsupporting
confidence: 68%
“…All of these early descriptive studies suggested that the parent-child interactions in the home played a significant role in how children understood the functions of literacy practices, which, in turn, influenced their academic development and achievement. Although a large body of family literacy scholarship recognizes the range of literacy practices found in diverse families and highlights parents' agency as they support their children (Compton-Lilly & Delbridge, 2019;Kirkland & Jackson, 2009;Tatum & Muhammad, 2012), many of these ethnographic investigations have missed the complexity of the family-child relationship, the technologies involved, and the racialized and ethnic contexts that mediated the expressions of literacy learning today (Compton-Lilly et al, 2012;Compton-Lilly et al, 2020). This article talks about these contextual aspects of family literacy learning during a time when "in school" literacies were fostered in students' homes, and when traditionally printed texts were scanned in and consumed digitally during the COVID-19 quarantine.…”
Section: Family Literaciesmentioning
confidence: 99%
“…Finally, principal literacy leaders foster a collaborative culture with and among educators and stakeholders. They provide a welcoming environment and promote collective responsibility in the literacy achievement of all students (Compton-Lilly & Delbridge, 2018; DeMatthews & Mawhinney, 2014; ILA, 2019; Jones et al, 2019; Khalifa, 2018; Riley & Webster, 2016; Salisbury & McGregor, 2005). The inclusion of families and the community in the literacy instruction of the students establishes collaborative partnerships, opens two-way lines of communication, fosters trust between the school and its stakeholders, and offers additional support systems for students (Brumley, 2010; Compton-Lilly & Delbridge, 2018; Crum, 2008; Houck & Novak, 2017; ILA, 2019; Khalifa, 2018; Khalifa et al, 2016; Plaatjies, 2019; Riley & Webster, 2016; Taylor, 2004).…”
Section: The Principal As Literacy Leadermentioning
confidence: 99%
“…They provide a welcoming environment and promote collective responsibility in the literacy achievement of all students (Compton-Lilly & Delbridge, 2018; DeMatthews & Mawhinney, 2014; ILA, 2019; Jones et al, 2019; Khalifa, 2018; Riley & Webster, 2016; Salisbury & McGregor, 2005). The inclusion of families and the community in the literacy instruction of the students establishes collaborative partnerships, opens two-way lines of communication, fosters trust between the school and its stakeholders, and offers additional support systems for students (Brumley, 2010; Compton-Lilly & Delbridge, 2018; Crum, 2008; Houck & Novak, 2017; ILA, 2019; Khalifa, 2018; Khalifa et al, 2016; Plaatjies, 2019; Riley & Webster, 2016; Taylor, 2004). Thus, principal literacy leaders use their knowledge of literacy and their school context to formulate a plan for high-quality literacy instruction that supports learning for all students (Cuticelli et al, 2016; Dowell et al, 2012; Hollenbeck & Rieckhoff, 2014; Khalifa, 2018; Khalifa et al, 2016; Overholt & Szabocsik, 2013; Teale et al, 2018).…”
Section: The Principal As Literacy Leadermentioning
confidence: 99%
See 1 more Smart Citation